Intensive Cropping in Egypt - Kamel, Ahmed Said (Annals of Arid Zone, 2016)
Intensification has numerous potential benefits to agriculture development in Egypt. To accelerate the rate of agricultural development, attention is now focused on optimizing the use of land resources, to satisfy the needs of increasing population, to reduce food and feed gaps and to increase farmer income. Intensive cropping in Egypt could be achieved through the application of non-traditional cropping s stems. The principles for the application of these approaches include using various mixed cultivation systems, using multiplicity of sequential cropping systems amounting to more than two crops per year. through the introduction of new agro-technologies in farming systems and applying innovative crop sequences and crop rotations. This paper includes a brief description of the problems to be solved, a brief justification and the critical gaps to b filled